The Effect Of Service Quality And Location On Yama Motor Customer Satisfaction - Jason Mulyadi; Tri Lestira Putri Warganegara (Cita konsultindo, 2025)
In an increasingly competitive business environment, the factor that really determines a company's success is customer satisfaction, including in the automotive industry such as Yama Motor. Customer satisfaction is influenced by various aspects, including service quality and location. Aims to evaluate the influence of service quality and location on customer satisfaction at Yama Motor. The quantitative method is implemented by applying multiple linear regression analysis. The population is those who have serviced motorbikes at Yama Motor and the sample involves 100 respondents with the Lameshow formula at a margin of 10%. Data was collected using a questionnaire distributed to customers at Yama Motor. These findings explain (1) the influence of service quality on customer satisfaction, (2) the influence of location on customer satisfaction, (3) the simultaneous influence of service quality and location on customer satisfaction. This research concludes that the combination of superior service quality and appropriate prices is a key factor in increasing customer satisfaction for Yama Motor. The company needs to continue to make improvements to its service standards and establish a competitive pricing strategy to strengthen customer loyalty. , the aim of this research is to identify the influence of service quality and location on customer satisfaction at Bengkel Yama Motor. It is hoped that it can enrich theoretical insight in the realm of service marketing management science and provide practical recommendations for workshop managers in improving service quality and determining optimal location strategies..